Helicobacter pylori Infection: From Pathogenesis to Clinical Management - Noor Adnan Mahmood; Olfat Raouf Mahmoud; Lubna Arkan Younis (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Helicobacter pylori represents a gram-negative bacterium colonizing gastric mucosa in approximately half of the global population, recognized as the primary causative agent of chronic gastritis, peptic ulcer disease, gastric cancer, and mucosa-associated lymphoid tissue lymphoma. Specific Background: The bacterium employs sophisticated virulence factors including cytotoxin-associated gene A and vacuolating cytotoxin A to establish chronic infection, triggering persistent inflammatory responses that progress through atrophic gastritis, intestinal metaplasia, and dysplasia toward malignancy. Knowledge Gap: Despite advances in understanding pathogenesis and treatment protocols, escalating antibiotic resistance threatens conventional eradication strategies, necessitating comprehensive evaluation of current diagnostic approaches and therapeutic interventions. Aims: This review systematically examines the microbiology, pathogenesis, epidemiology, clinical manifestations, diagnostic methods, and treatment strategies for H. pylori infection, with particular emphasis on antibiotic resistance patterns. Results: Evidence demonstrates that bismuth-based quadruple therapy achieves 80-90% eradication rates even in clarithromycin-resistant regions, while H. pylori eradication significantly reduces gastric cancer risk when implemented before precancerous lesion development. Novelty: The analysis integrates molecular resistance mechanisms with population-based epidemiological patterns to inform personalized treatment selection. Implications: Sustained multidisciplinary collaboration remains essential for developing novel antibiotics, rapid susceptibility testing, and effective vaccines to reduce global H. pylori disease burden.Keywords : Helicobacter Pylori, Gastric Cancer, Peptic Ulcer Disease, Antibiotic Resistance, Diagnostic MethodsHighlight : Bacterium infects approximately 4.4 billion individuals worldwide with varying regional prevalence rates. Clarithromycin resistance reaches 50% in some regions, reducing triple therapy effectiveness significantly. Early eradication prevents gastric cancer progression when administered before precancerous lesion onset.